EXPERIMENTAL ANALYSIS OF PRECURSORS TO SEVERE PROBLEM BEHAVIOR. Issue 1 (1st April 2013) - Fritz, Jennifer N.; Iwata, Brian A.; Hammond, Jennifer L.; Bloom, Sarah E.
Abstract Some individuals engage in both mild and severe forms of problem behavior. Research has shown that when mild behaviors precede severe behaviors (i.e., the mild behaviors serve as precursors), they can (a) be maintained by the same source of reinforcement as severe behavior and (b) reduce rates of severe behavior observed during assessment. In Study 1, we developed an objective checklist to identify precursors via videotaped trials for 16 subjects who engaged in problem behavior and identified at least 1 precursor for every subject. In Study 2, we conducted separate functional analyses of precursor and severe problem behaviors for 8 subjects, and obtained correspondence between outcomes in 7 cases. In Study 3, we evaluated noncontingent reinforcement schedule thinning plus differential reinforcement of alternative behavior to reduce precursors, increase appropriate behavior, and maintain low rates of severe behavior during 3 treatment analyses for 2 subjects. Results showed that this treatment strategy was effective for behaviors maintained by positive and negative reinforcement.